Democracy and the state in the new southern Europe - Gunther, Richard; Diamandouros, Nikiforos P.; d (Oxford : Oxford University Press, 2006)
Analysing the evolution of selected public policies and the changing roles and structure of the state in Greece, Italy Portugal, and Spain since the 1960s, this volume makes a major contribution to work on democratic regime transition in southern Europe.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Democracy -- Europe, Southern; Europe, Southern -- Politics and government -- 20th century